Evaluación de la calidad de los suelos de la zona urbana de Loja,a través de índices de calidad de suelos basados en servicios ecosistémicos - Morocho Pullaguari, Alan Geovanny (2024)
Urban vegetation, as well as soil, provides us with ecosystem services (ES) and contributes to human well-being. In addition, it plays an important role in mitigating major urban environmental problems such as air pollution and noise attenuation. However, there are few studies on the assessment of urban soil quality based on ecosystem services and soil multifunctionality. In this study, the soil condition of 18 green areas in Loja was evaluated through the creation and development of an urban soil quality index (SQI), which was designed to provide a detailed soil evaluation. The database of scientific articles published between 1992 and 2022, obtained from the Web of Science, was used for this purpose. A bibliometric study was carried out, using the "Bibliometrix" R library, which made it possible to identify the ES and the indicators that best represent urban soil quality. A total of 13 indicators were considered; the indicators with the highest correlation were selected by using factor analysis, the selected ones being: pH, MO, N, P, and Ca. The SQI was calculated by considering the arithmetic mean of the indicators, which were obtained through mathematical functions. The SQI successfully identified the sites of low soil quality among the 18 green areas with different spatial types (line and polygon). As a result, Av. 8 de diciembre was the area with the lowest soil quality index (0.13); on the other hand, Parque Infantil was the area with the highest soil quality index in the city (0.35). Moreover, the SQI can help urban stakeholders evaluate and monitor the soil quality of urban vegetation in Loja.